2007
DOI: 10.1002/ppul.20732
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein in children with obstructive sleep apnea and the effects of treatment

Abstract: Summary. Objective To evaluate C-reactive protein (CRP) concentration in children with OSA and to determine the effects of treatment for OSA on its serum concentration. Methods Consecutive children with habitual snoring and symptoms suggestive of OSA were recruited. They completed a sleep apnea symptom questionnaire, underwent physical examination and an overnight polysomnography (PSG). Fasting serum CRP and lipid profile were taken after overnight PSG. OSA was diagnosed if obstructive apnea index (OAI) > 1. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 33 publications
2
36
0
3
Order By: Relevance
“…Four studies (including 2 from the same center) showed no relationship between CRP and OSAS, 71-74 whereas 4 studies (2 from the same center) did show a relationship. 46,[75][76][77] Part of the discrepancy between studies may be attributable to the varying proportions of obese subjects (because obesity is associated with high CRP levels) and varied age of subjects and definitions of OSAS in the different studies. Some studies controlled for obesity and degree of OSAS, whereas others did not.…”
Section: Inflammationmentioning
confidence: 99%
“…Four studies (including 2 from the same center) showed no relationship between CRP and OSAS, 71-74 whereas 4 studies (2 from the same center) did show a relationship. 46,[75][76][77] Part of the discrepancy between studies may be attributable to the varying proportions of obese subjects (because obesity is associated with high CRP levels) and varied age of subjects and definitions of OSAS in the different studies. Some studies controlled for obesity and degree of OSAS, whereas others did not.…”
Section: Inflammationmentioning
confidence: 99%
“…CRP dropped after tonsillo-adenoidectomy in children. 7 Other factors that might be involved in atherosclerosis, like fibrinogen level and p-selectin (marker of platelet activation), were shown to be higher in those with OSA.…”
Section: Re: the Association Between Hay Fever And Stroke In A Cohortmentioning
confidence: 98%
“…Повышение уровня С-реактивного белка на фоне обструктивного апноэ сна выявлено как у взрослых [48], так и у де-тей [49]. Снижение его уровня отмечено при эффек-тивном лечении апноэ сна у детей [50]. Повышение показателя С-реактивного белка и иных медиато-ров воспаления на фоне обструктивного апноэ сна у детей, как полагают, во многом модифицируется влиянием генетических факторов [51].…”
Section: российский вестник перинатологии и педиатрии 4 2016unclassified